Chromogranin A preferential interaction with Golgi phosphatidic acid induces membrane deformation and contributes to secretory granule biogenesis. Issue 5 (29th March 2020) - Carmon, Ophélie; Laguerre, Fanny; Riachy, Lina; Delestre‐Delacour, Charlène; Wang, Qili; Tanguy, Emeline; Jeandel, Lydie; Cartier, Dorthe; Thahouly, Tamou; Haeberlé, Anne‐Marie; Fouillen, Laetitia; Rezazgui, Olivier; et al.
Abstract: Chromogranin A (CgA) is a key luminal actor of secretory granule biogenesis at the trans ‐Golgi network (TGN) level but the molecular mechanisms involved remain obscure. Here, we investigated the possibility that CgA acts synergistically with specific membrane lipids to trigger secretory granule formation. We show that CgA preferentially interacts with the anionic glycerophospholipid phosphatidic acid (PA). In accordance, bioinformatic analysis predicted a PA‐binding domain (PABD) in CgA sequence that effectively bound PA (36:1) or PA (40:6) in membrane models. We identified PA (36:1) and PA (40:6) as predominant species in Golgi and granule membranes of secretory cells, and we found that CgA interaction with these PA species promotes artificial membrane deformation and remodeling. Furthermore, we demonstrated that disruption of either CgA PABD or phospholipase D (PLD) activity significantly alters secretory granule formation in secretory cells. Our findings show for the first time the ability of CgA to interact with PLD‐generated PA, which allows membrane remodeling and curvature, key processes necessary to initiate secretory granule budding.